Workers, peasants and citizens: Factors of female political adhesion in Chile (1965-1973) - Arias, Tomás (Revista de Historia Social y de las Mentalidades, 2025)
This study analyzes how social and structural factors influenced women’s political adherence to the left, center, and right between 1965 and 1973. Through electoral data, surveys and censuses, the relationship between labor force participation, educational levels, religion and marital status with women’s political preferences was examined. The results showed that the sectors with more female workers in the centre had better voting. The left achieved better votes in provinces with less female illiteracy. The Catholic religion showed an inclination to the right. Married women tended to identify with the left, possibly because of more socially traditional values in the lower classes than among affluent women. This study enriches the understanding of female political behavior in Chile before 1973.